Microemulsion with ester in mixed surfactants and its association with betulinic acid - Wan Mahamod, Wan Rusmawati (2000)
The phase behaviour of Tween 80IBrij 301H20 and Tween 80/Brij 30/glycerol was constructed to determine the isotropic region produced by the mixed surfactants (MS) - Tween 80:Brij 30 - in aqueous and nonaqueous systems. The weight ratios of 90: 10, 80:20 and 60:40 Tween 80:Brij 30 were selected for further construction of MS systems of MA or EB/Tween 80:Brij 30lwater and MA or EB/Tween 80:Brij 30/glycerol. M S in aqueous systems produced a larger isotropic region than the single phase MA or EB/Tween 80lwater and MA or EB/Brij 30lwater systems. The system of MA/Tween 80:Brij 30 (90: 10, 80:20 and 6O:40)lwater was then studied to determine the surfactants' aggregation and their association with BA. The conductivity was measured to assess the charge carrier and the movement of ions in the system. The structure of the isotropic region was also deterrnined. A reverse micelle (w/o micromulsion), bicontinuous structure and micelle (o/w microemulsion) formed in the range of 20 - 40wt%, 40 - 60wt% and >60wt% water, respectively. However, the MA/Tween 80:Brij 30 (80:20)/water system did not form a micelle. The results were confirmed by light scattering measurement in which the particle size in each region was determined. BA was more soluble in the system with higher Tween 80. The solubility of BA increased with the MA content and decreased with the water content. In the antimicrobial study, 0.01 wt% BA in the microemulsion MA/Tween 80:Brij 30 (80:20)/water was more active against Candida lipolytica ATCC 2075 than the pure microemulsion itself. A higher mixed surfactant content (20:80 weight ratio of MA and MS) gave better activity than a lower one (50 :50 weight ratio). BA in the reverse micelle region gave the highest activity compared to in the monomer and bicontinuous regions. The cytotoxicity study produced unexpected results. The microemulsion systems were very active and killed all the cells (CEM-SS) leaving no control data with which to assess the cytotoxicity.